Efeito da adição de cal em argamassa na resistência à corrosão de armaduras de aço carbono e galvanizadas - Michele Candida Carvalho de Oliveira (2013)
The civil construction industry has up grown in recent years, and with this, the use of reinforced concrete. Corrosion of reinforcement in concrete structures is a major problem that affects the integrity of the concrete. Therefore, studies are required in order to contribute to minimize the losses involved in the corrosion of reinforcement in concrete. The alkaline environment of the concrete allows the protection of reinforcement by passivation. Once the lime present in the mortar helps to raise the alkalinity of the concrete, the aim of this work is to study the effect of adding lime in the mortar, analyzing the corrosion of reinforcing carbon steel and galvanized carbon steel wires. The contents of lime of 26.3%, 13.3% and 6.7% (wt) were added in mortar, and the corrosion potentials of reinforced mortar, with and without lime addition, were measured before and after the corrosion test of immersion in saline solution 3.5% (wt) of NaC. Measurements of polarization resistance of steels in reinforced mortar with different contents of lime were performed using electrochemical impedance spectroscopy. The beneficial effect of lime addition was observed, increasing the corrosion potential and the polarization resistance of carbon steel, and galvanized carbon steel. After the immersion of samples in saline solution, a reduction of the corrosion potential of galvanized and carbon steels was identified. Measurements of the open circuit potential and electrochemical impedance spectroscopy were repeated after 36 months to verify the influence of time in the process of reinforcement corrosion.